Effect of surfactants on the properties of rubber composites prepared from pyrolytic carbon black/natural latex via wet blending method - Song, Xiudong; Wang, Kongshuo; Shan, Tilun; Wang, Chuansheng; Tian, Xiaolong (Frontiers in Materials, 2023)
Pyrolytic carbon black (CBp) is the main by-product of waste tire pyrolysis. CBp has high ash content and poor surface activity which leads to the composites reinforced with CBp has lower performance than composites reinforced with commercial carbon black, making it difficult to meet the requirements of tire. In order to realize the application of CBp in tires, the effect of surfactants on the properties of rubber composites prepared by wet mixing of CBp/natural latex was investigated. In the experimental process, sodium stearate (C17H35COONa), sodium dodecylbenzene sulfonate (C18H29NaO3S), and sodium p-styrenesulfonate (C8H7NaO3S) were used to improve the surface activity and uniform dispersion of the CBp in the natural rubber matrix. The experimental results showed that the dispersity of C18H29NaO3S and C8H7NaO3S modified CBp in rubber matrix has [X] and [Y] values of 7.5 and 7.9, and 9.3 and 9.5, respectively, and the dispersion of these rubber composites is significantly better than that of C17H35COONa. The rubber composites prepared by C18H29NaO3S and C8H7NaO3S surfactants has the better physical and mechanical properties. The rubber composite prepared by C18H29NaO3S has the highest tensile strength of 25.63 MPa, which increment in tensile strength is 15.6% compare to the rubber composite prepared by C17H35COONa. Meanwhile the dynamic mechanical properties of rubber composites prepared by modifying CBp with C18H29NaO3S and C8H7NaO3S are better than CBp with C17H35COONa. The C8H7NaO3S modified CBp/rubber composite has the lowest loss factor (tanδ) value at 60 °C, and the C18H29NaO3S modified CBp/rubber composite has the highest tanδ value at 0 °C.